Role of Endoscopic Procedure in Foreign Body (Button Battery) Ingestion in Children: A Case Report - Harsali Lampus; Candy Candy; Leo Rendy; Andy A. Rangan (Medical Scope Journal, 2023)
Abstract: Foreign body (FB) ingestion is a common problem especially in children below the age of 5 years. Due to the extensive use of batteries as power supply in electronic gadgets, cases of button battery ingestion have become more common. If a button battery was found in the stomach of a child under the age of five, it should be assessed for esophageal injury and removed endoscopically, if at all possible, within 24 to 48 hours. We reported a 3-year-old boy who swallowed a foreign body three hours before being admitted to the hospital. Initially the patient was playing with robot toys that used batteries, then a battery of the robots was accidently swallowed. The patient had no symptoms and physical examinations showed no abnormalities. Abdominal X-ray examination revealed a foreign body located in the stomach. The patient underwent endoscopic foreign body removal but no foreign body was found until the second part of duodenum. Therefore, an exploratory laparotomy was performed, and the foreign body, a button battery, was removed from the ileum. In conclusion, since endoscopic foreign body removal failed to remove the foreign body in this patient, an exploratory laparotomy was performed and through antimesenterial ileotomy, the foreign body, a button battery, was successfully removed. Keywords: foreign body; endoscopic foreign body removal; exploratory laparotomy